Feeling grateful and envious: adolescents' narratives of social emotions in identity and social development*. Issue 3 (2nd July 2016) - Poelker, Katelyn E.; Gibbons, Judith L.; Hughes, Honore M.; Powlishta, Kimberly K.
Abstract: Although the ubiquity of gratitude and envy would suggest they are important in the daily lives of adolescents, those social emotions have been relatively unexplored by psychologists. Interviews of 25 adolescents (ages 14 through 16) from the Midwestern US provided narrative accounts that revealed the contexts, antecedents, consequences and meanings of gratitude and envy in their daily lives. Transcripts were coded using an established procedure in the literature, and we present the findings at the thematic level. Adolescent gratitude was characterised by feeling cared for and special, while envy was driven by the desire for material possessions. Both emotions may reflect cultural individualism and contribute to social and identity development; for those adolescents gratitude provides recognition and validation of one's personhood, and envy creates negative social comparisons that can either diminish self-worth or provide the impetus for improvement.